173-OR: A Clinical Study of Novel Antimicrobial Peptide PL-5 Topical Spray for Mild to Moderate Infectious Wounds of Diabetic Foot - QIAN, LI; WANG, AIPING; HU, WEN; WANG, GUOFENG; SUN, XINJUAN; LIU, YU (Diabetes (New York, N.Y.), 2024)
Background: Antimicrobial peptide PL-5 spray is a topical antimicrobial peptide drug with novel mechanism of action and may improve the cure efficiency of diabetic foot infections. We studied the clinical efficacy and safety of investigational PL-5 spray in the treatment of mild to moderate diabetic foot ulcers in combined with standard debridement procedure. Methods: A multicenter, randomized, double-blind, placebo-controlled clinical trial was conducted in four hospitals in China. Qualified subjects with mild to moderate diabetic foot ulcers were randomly assigned (2:1 ratio) into PL-5 and placebo groups plus a standard debridement. The primary endpoint of the study was the clinical efficacy at day 1 after the end of treatment (EOT1); the secondary endpoints included the clinical efficacy of treatment at day 7 after EOT(EOT7), microbiological efficacy, drug-resistant bacteria clearance rate, wound healing rate, and safety outcomes evaluated at EOT1 and EOT7, respectively. Results: Subjects in PL-5 and placebo groups (32 vs 15 cases) showed no statistical differences in demographic and clinical characteristics. The clinical efficacy (cure/improvement ratio) in PL-5 group at EOT1 was higher than that in control group (1.33 vs 0.55, p=0.0764). Among the secondary endpoints, the clinical efficacy at EOT7 in PL-5 and control groups were 1.6 vs 0.86, the microbial eradication rates were 57.89% vs 33.33% (EOT1) and 64.71% vs 40.00% (EOT7); the drug-resistant bacteria clearance rates were 71.43% vs 50% (EOT1), respectively. The safety parameters showed no difference between two groups (24.24% vs 33.33%). Conclusion: With limited samples, antimicrobial peptide PL-5 spray still shows strong potentials on efficacy and safety against the wound infections caused by drug-resistant bacteria. It can be anticipated that topical PL-5 treatment significantly improved the recovery speed of the diabetic foot wounds in further amplified study.